Laryngeal handshake technique in locating the cricothyroid membrane: a non-randomised comparative study. (November 2018) - Drew, T.; McCaul, C.L.
Abstract: Background: Evaluation of the anterior neck anatomy is used to identify the cricothyroid membrane (CTM) before front of neck airway access. This has been traditionally performed using palpation which results in misidentification of the CTM in a high proportion of subjects. The 'laryngeal handshake' is currently advocated by the Difficult Airway Society as the method to identify the CTM. We sought to investigate the accuracy of this technique in females. Methods: Five clinicians were asked to identify the CTM using the 'laryngeal handshake' technique in a total of 45 anaesthetised females (Group L) and by conventional palpation in 45 controls (Group P). We measured and analysed the distance to actual CTM using ultrasound, the time to identification, and perceived difficulty using a visual analogue scale. Results: Successful identification of the CTM occurred in 28/45 (62%) patients in Group L vs 15/45 (33%) in Group P [ P =0.006; mean difference, 29%; 95% confidence interval (CI), 21–39%]. Distance to the CTM ( P =0.012) and visual analogue scale ( P =0.012) were significantly reduced in Group L. Mean time to CTM identification was greater in Group L at 31 (5.6) s, compared with Group P, which took 18 (5.5) s ( P <0.001). The midline was accurately identified more frequently in Group L than in Group P (39/45 vs 28/45, P =0.008). Conclusions: The 'laryngeal handshake' method of palpation is more accurate but takes longer than conventional palpation technique in locating the CTM and the midline. This is of particular relevance if a vertical incision is required to perform front of neck access when anatomy is indistinct.